2000
DOI: 10.1080/003655200750022968
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Helicobacter heilmannii-associated Gastritis in a Small, Predominantly Rural Area: Further Evidence in Support of a Zoonosis?

Abstract: A high prevalence of H. heilmannii-associated gastritis in a small, predominantly rural area and statistically significant differences in prevalence from one community to the next, i.e. highest in the smallest village and lowest in a small town with a rather urban lifestyle, were found. In our opinion, these prevalence rates may be a consequence of transmission of the infection from domestic animals, because animal-human contact is generally more common in villages than in towns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Chronic gastritis was the most common histologic finding in our cohort, employing a well-validated gastritis scoring tool (i.e., the Updated Sydney system), consistent with previous reports. 9,22,23,[35][36][37][38][39] Compared to H. pylori, H. heilmannii-associated chronic gastritis is considered to be more focal, milder, and restricted to the antrum. 40 In our study, we also found H. heilmanniiassociated chronic gastritis to have a milder degree of inflammation compared with H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic gastritis was the most common histologic finding in our cohort, employing a well-validated gastritis scoring tool (i.e., the Updated Sydney system), consistent with previous reports. 9,22,23,[35][36][37][38][39] Compared to H. pylori, H. heilmannii-associated chronic gastritis is considered to be more focal, milder, and restricted to the antrum. 40 In our study, we also found H. heilmanniiassociated chronic gastritis to have a milder degree of inflammation compared with H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…The exact route of NHPH transmission from animals to humans is not yet clears [ 3 ]. Several studies showed that living in close proximity to as well as intense contact with infected dogs, cats, and pigs leads to a significant risk of NHPH infection [ 33 , 34 ]. Helicobacter DNA has been detected in saliva and faeces from cats and dogs [ 35 ], indicating that oral-oral and oral-faecal contact may be a route of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Alhoewel het niet exact bekend is hoe gastrale NHPH overgedragen worden van dieren naar mensen, gebeurt dit allicht vooral door direct contact. Verschillende epidemiologische studies hebben inderdaad aangetoond dat mensen die in nauw contact leven met honden, katten en vooral varkens meer kans hebben om besmet te raken met deze spiraalvormige bacteriën (Holck et al, 1997;Meining et al, 1998;Svec et al, 2000). Recentelijk werd aangetoond dat helicobacters meer dan 4 dagen kunnen overleven in water.…”
Section: Zijn Dieren Een Bron Van Infectie Met Gastrale Niet-h Pylori...unclassified